Research of Preparation Conditions for Regeneration of Hydroxyapatite and Influence on Crystalline Forms - Wei Song; Yan Yang; Yu Deng (Kemija u Industriji, 2018)
The process of hydroxyapatite (HAp) precipitation in ionic liquid (ChCl-urea) was studied and the influence of various factors on the crystalline forms and yields of HAp were analysed. It was concluded that Na-citrate made the regenerated HAp appear as a long cylindrical crystal (perfect rod-like grain) when chosen to be an additive/surfactant. The optimum conditions for HAp precipitation (regenerated HAp) were applied to extract HAp from chicken bone in ChCl-urea (product HAp). The product HAp was characterized by FTIR, SEM XRD and Particle Size Analyser. The results showed that there is no obvious difference between HAp extracted from chicken bone (product HAp) and regenerated HAp regarding crystalline forms and compositions. The product HAp is relatively pure, and its average particle size is 555.6 nm, meaning that this product has the application value.